(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Background: With the increased use of internet, concerns are also being raised about the negative effects of internet particularly in the young population. Students are particularly susceptible to the negative physical and psychological effects of internet. With this background we aimed to study the problematic internet use and its association with sleep quality in undergraduate students of BP Koirala Institute of Health Sciences (BPKIHS). Methodology: A descriptive cross sectional study was conducted among the undergraduate students of BPKIHS. An online form consisting of sociodemographic profile, Young’s Internet Addiction Test (IAT) and Pittsburgh Sleep Quality Index (PSQI) was distributed among the students. Results: A total of 235 responses were obtained. The mean age of participants was 22.52 years ± 1.851. Majority of the participants were males (61.3%) and from third year of study program (32.3%). Problem internet use was found to be present in 211 (89.8%) of the participants with 163 (69.4%) and 48 (20.4%) having mild and moderate addiction respectively. 83(35.3%) students reported to have a disturbed sleep pattern. A significant association was found between problematic internet use and sleep problems (p value <0.01). A moderately positive co-relation was found between IAT and PSQI scores (r value=0.4, p value <0.01). Conclusion: Problematic internet use is a highly prevalent phenomenon among medical undergraduates and is significantly associated with poor sleep quality. Effective measures need to be taken to educate students about internet use and sleep hygiene.